Perencanaan Infrastruktur Gedung Kantor Dengan Konsep Rumah Betang Modern Untuk Optimalisasi Pelayanan - Muhammad Nanda Arya Putra; Mei Yuliani; Reynaldo Kristy; Dela Meinita; Daniel Delon Tilaar; Desi Riani (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
Pahandut Subdistrict, as the primary activity center in Palangka Raya City, faces public service constraints due to inadequate physical office conditions to accommodate high visitor volumes. This community service activity, conducted through the "Teknik Membangun dan Berdampak" (TMB) program, aims to design office infrastructure capable of managing high population density and modern service standards. The implementation method was participatory, involving field surveys, intensive discussions, and digital modeling using SketchUp and AutoCAD software. The results include comprehensive technical planning documents featuring a "Modern Rumah Betang" concept that adapts open-plan layouts and linear circulation to optimize service flow and thermal comfort amidst high-density activities. The documents comprise Detailed Engineering Design (DED) drawings and a Budget Plan (RAB) totaling Rp 14,160,815,000.00. These documents serve as a technical foundation for the local government to enhance inclusive and representative public service quality in Pahandut Subdistrict.